2009
DOI: 10.1016/j.str.2009.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Secondary Structure of Huntingtin Amino-Terminal Region

Abstract: Summary Huntington's disease (HD) is a genetic neurodegenerative disorder resulting from polyglutamine (polyQ) expansion (> 36Q) within first exon of Huntingtin (Htt) protein. Here we applied X-ray crystallography to determine the secondary structure of the first exon (EX1) of Htt-17Q. The structure of Htt17Q-EX1 consists of an amino-terminal α-helix, a poly17Q region, and a polyproline helix formed by the proline-rich region. The poly17Q region adopts multiple conformations in the structure, including α-helix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
294
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 227 publications
(337 citation statements)
references
References 48 publications
37
294
1
2
Order By: Relevance
“…Unfortunately, these studies have reported contradictory observations regarding the conformational preferences of the HR. Similar observations have been obtained from crystallographic studies of non‐aggregated poly‐Q constructs: while a peptide of 10 consecutive glutamines in complex with an antibody showed an extended structure,14 a construct with 17 Qs in the context of htt exon1 showed multiple conformations (helix, random coil, and extended loop), and only the initial residues were visible on the map 15. More recently, Baias et al.…”
supporting
confidence: 76%
“…Unfortunately, these studies have reported contradictory observations regarding the conformational preferences of the HR. Similar observations have been obtained from crystallographic studies of non‐aggregated poly‐Q constructs: while a peptide of 10 consecutive glutamines in complex with an antibody showed an extended structure,14 a construct with 17 Qs in the context of htt exon1 showed multiple conformations (helix, random coil, and extended loop), and only the initial residues were visible on the map 15. More recently, Baias et al.…”
supporting
confidence: 76%
“…Our studies indicate a role of Nt17 in the interaction between htt and lipid membranes. Nt17 forms an amphipathic ␣-helical structure (20), which can influence the first few glutamines in the poly(Q) domain to adopt an ␣-helical conformation (41). The amphipathic properties of the Nt17 ␣-helix (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A solved crystal structure of the HTT exon 1 gene product with 17 glutamine repeats fused with maltose binding protein shows that the NT17 segment becomes α-helical (29). The NT17 tract has been shown to be critical for the formation of α-helix-rich oligomeric intermediates by Jayaraman et al (14).…”
Section: N-terminal Region Facilitates the Aggregation Of Nt 17 -Q 20mentioning
confidence: 99%